Ús lingüístic, legitimitat i discurs: consideracions weberianes - Calaforra, Guillem (Caplletra. Revista Internacional de Filologia, 2004)
The “psychosociological turn” of the sociology of language entails a newattention paid to the role of agency in language use. But this new approach can be coherent and complete only by taking into account the historical and politicalcircumstances of language use, as well as the whole set of factors determining the processes by which social meanings are created and distributed. On the basis of the Weberian concept of legitimacy, this paper tries to outline the characteristics of the relationship between social discourses and the patterns of language use. It ends with some reflections on the utility and the difficulties of using critical discourse analysis in order to understand the symbolic side of language use.